Agriculture, environment, and health : sustainable development in the 21st century - Ruttan, Vernon W. (University of Minnesota Press, 1994)
Offers an interdisciplinary exploration of the implications of changes in institutional design and policy reform now underway at the global level. Particular attention is given to the institutions that conduct research and implement changes in technology and practice in the fields of agriculture and health, as well as those that monitor the changes in resource endowments, the quality of the environment and the health, and productivity of the human resources employed in agricultural production.